2020
DOI: 10.1038/s41375-020-0773-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of talacotuzumab plus decitabine or decitabine alone in patients with acute myeloid leukemia not eligible for chemotherapy: results from a multicenter, randomized, phase 2/3 study

Abstract: Talacotuzumab, a humanized anti-CD123 monoclonal antibody, was evaluated in combination with decitabine in elderly patients with acute myeloid leukemia (AML) not eligible for intensive chemotherapy. A multicenter, phase 2/3 study was initiated to determine the recommended phase 2 dose (RP2D) of talacotuzumab (Part A) followed by an open-label, randomized comparison of talacotuzumab in combination with decitabine versus decitabine alone to assess achievement of complete response (CR) and overall survival (OS) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 21 publications
0
64
0
Order By: Relevance
“…The study was initially powered to include a total of 43 patients, but the SAMBA trial was prematurely terminated because the manufacturer decided to stop the entire TAL study program due to lack of efficacy and high toxicity rates in a pivotal study involving TAL in combination with DAC as first line treatment in AML (NCT02472145) [13]. Consequently, only 24 patients (19 AML and 5 HR-MDS) with a median age of 77 years (range 71-90) who either failed to achieve CR, PR, HI, or relapsed after at least six AZA or four DAC treatment cycles were included in the study from November 2016 until June 2017.…”
Section: To the Editormentioning
confidence: 99%
“…The study was initially powered to include a total of 43 patients, but the SAMBA trial was prematurely terminated because the manufacturer decided to stop the entire TAL study program due to lack of efficacy and high toxicity rates in a pivotal study involving TAL in combination with DAC as first line treatment in AML (NCT02472145) [13]. Consequently, only 24 patients (19 AML and 5 HR-MDS) with a median age of 77 years (range 71-90) who either failed to achieve CR, PR, HI, or relapsed after at least six AZA or four DAC treatment cycles were included in the study from November 2016 until June 2017.…”
Section: To the Editormentioning
confidence: 99%
“…66 In a recent trial, talacotuzumab, a humanized anti-CD123 antibody, was administered in combination with decitabine in older AML patients not eligible for poly-chemotherapy. 67 However, the drug combination did not result in a better outcome compared to decitabine alone. 67 Other surface targets that have been considered in the context of AML and antibody-mediated elimination of LSC include CD44, CD45, CD47, CD93, CD96, CD157, CD330f, and CLL-1.…”
Section: Antigen CDmentioning
confidence: 93%
“…67 However, the drug combination did not result in a better outcome compared to decitabine alone. 67 Other surface targets that have been considered in the context of AML and antibody-mediated elimination of LSC include CD44, CD45, CD47, CD93, CD96, CD157, CD330f, and CLL-1. 8,[30][31][32][33][34]38,43,[68][69][70] However, so far, no major AML-eradicating activity was obtained in clinical trials.…”
Section: Antigen CDmentioning
confidence: 93%
See 1 more Smart Citation
“…Only 10% of patients achieved CR on combination therapy compared to 11% of patients receiving decitabine alone, resulting in early termination of enrollment and discontinuation of treatment. 375 Noted in these studies was the limitation of patients' natural killer (NK) lymphocytes present and preclinical studies have suggested the use of human allogeneic NK cells in combination with talacotuzumab to promote NK cell antibodydependent cell-mediated cytotoxicity. 376 Another way to improve cytotoxicity of mAb therapies is using a CD123-targeting ADC.…”
Section: Targeting Signaling Pathways In Lscsmentioning
confidence: 99%